Hubungan Ketahanan Pangan Keluarga Dengan Status Gizi Balita (Studi Di Desa Palasari Dan Puskesmas Kecamatan Legok, Kabupaten Tangerang) - Afrizal Arlius; Toto Sudargo; Subejo Subejo (Jurnal Ketahanan Nasional, 2017)
ABSTRACTThis study aims to (1) to examine the relationship of food security with the nutritional status of children under  five in the working area of Puskesmas Legok, Legok Subdistrict, Tangerang District. (2) to study the variety of efforts to improve food security in malnutrition prevention of children under five in the working area of Legok Puskesmas, Legok Subdistrict, Tangerang District. The population in this study were parents / mothers / fathers and children aged 0-59 months who suffered malnutrition and malnutrition (under normal conditions). The results of the study showed that: (1) Some respondents were in food insecurity category, about 36 %, In food sensitive category about 39% and foodstuff category only about 15% and less food category about 10%. (2) Community nutrition improvement program or toddlers Legok Puskesmas conducted daily, monthly and yearly, daily program are: Increasing exclusive breastfeeding without additional food and drinks for babies up to 6 months old. The monthly program is monitoring the development of underweight body weight (weighing the balita) which is weighing weight measurement of toddler to know growth pattern and growth of toddler body and its development. The annual program is monitoring the nutritional status of children under five and monitoring nutrition nutrient intake.Food security and nutritional status of toddlers are closely related, if the family of food security enough to affect the nutritional status so good, otherwise if the food is less then the nutritional status is likely to experience malnutrition and lack of nutritionABSTRAKPenelitian bertujuan ini adalah (1) untuk mengkaji hubungan ketahanan pangan dengan status gizi balita di wilayah kerja Puskesmas Legok, Kecamatan Legok, Kabupaten Tangerang. (2) untuk mengkaji ragam upaya meningkatkan ketahanan pangan dalam penanggulangan gizi buruk balita di wilayah kerja Puskesmas Legok, Kecamatan Legok, Kabupaten Tangerang. Populasi dalam penelitian ini adalah orang tua/ ibu/ bapak dan balita umur 0-59 bulan yang menderita gizi buruk dan kurang gizi (di bawah kondisi normal).Hasil penelitian menunjukkan bahwa: (1) Sebagian responden berada dalam kategori rawan pangan, sekitar 36%, pada kategori rentan pangan sekitar 39% dan kategori tahan pangan hanya sekitar 15% serta kategori kurang pangan sekitar 10%. (2) Program peningkatan gizi masyarakat atau balita Puskesmas Legok dilaksanakan secara harian, bulanan dan tahunan, program harian adalah : Peningkatan pemberian Air Susu Ibu (ASI) eksklusif tanpa makanan dan minuman tambahan  untuk   bayi  berumur sampai umur 6 bulan. Program bulanan adalah pemantauan Perkembangan berat badan balita (Penimbangan  badan balita) yaitu penimbangan  pengukuran berat badan balita untuk mengetahui pola pertumbuhan dan perkembangan badan balita dan perkembangannya. Program tahunan adalah Pemantauan status gizi balita dan pemantauan asupan gizi gizi.Ketahanan pangan dan status gizi balita terdapat hubungan yang erat, jika keluarga ketahanan pangannya cukup akan mempengaruhi status gizinya jadi baik, sebaliknya jika pangannya kurang  maka status gizinya kemungkinan akan mengalami gizi buruk dan kurang